Pengaruh Motivasi dan Budaya Organisasi terhadap Kinerja Karyawan - Agus Cahyadi, I Gusti Ngurah; Susanti, Putu Herny; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The success of a business, both groups and individuals, is largely determined by the human resources in it. Optimal human resources will be able to realize the company's goals, namely to get profits. This study aims to determine the effect of motivation and organizational culture on employee performance. This research was conducted at the Depo Bagoes Bangunan. The number of samples is 95 respondents determined using the saturated sample method. Data collection was carried out by observation, interviews, and questionnaires. Based on the results of the study it can be seen that motivation has a positive and significant effect partially on employee performance. Organizational culture has a positive and significant effect partially on employee performance. Motivation and organizational culture simultaneously have a significant effect on employee performance. This shows that the better the motivation and organizational culture, the higher the performance of its employees. However, in the future, the Depo Bagoes Bangunan must pay attention to the amount of incentives distributed to employees in accordance with employee achievements so that later employees are motivated to continue to work even better.